In search of pedagogical content knowledge in science: Developing ways of articulating and documenting professional practice - Loughran, John; Mulhall, Pamela; Berry, Amanda (Journal of research in science teaching, 2004)
This study examines the development of ways of documenting and portraying science teachers' pedagogical content knowledge (PCK). As a result of a longitudinal study into science teachers' pedagogical content knowledge, a method is developed for capturing and portraying PCK that comprises two important elements. The first is linked to the particular science content, termed Content Representation (CoRe), and the second is linked to teaching practice, termed Professional and Pedagogical experience Repertoire (PaP-eR). Through this approach new understandings of PCK emerge that are of interest in terms of both academic (knowledge building about PCK) and teaching perspectives. This study includes a full CoRe and one PaP-eR and fully demonstrates how these two elements interact to begin to portray science teachers' pedagogical content knowledge. [Author abstract]